Evaluation of the Effectiveness of Mental Health Education Programs for Mentally Disordered Patients: Qualitative Research with a Phenomenological Approach - Bambang Irawan; Sisilia Prima Yanuaria Buka; Murphy Xavier; McCarty Elliot; Meredith Tandon (Journal of World Future Medicine, Health and Nursing, 2024)
Mental health education programs have an important role in increasing the understanding and skills of patients experiencing mental disorders. This study aims to evaluate the effectiveness of mental health education programs for patients with mental disorders through a qualitative approach using phenomenological methods. The research background highlights the need for a holistic approach to the management of mental disorders, with an emphasis on comprehensive education and understanding. The aim of this study was to understand patients' subjective experiences of a mental health education program and to evaluate its impact on improving their well-being. The research method used involves a qualitative approach with a phenomenological approach. Data was collected through in-depth interviews and participant observation. Data analysis was conducted thematically to identify common patterns in participant experiences and program impact. The research results show that mental health education programs make a positive contribution to increasing patients' understanding of their condition, strengthening coping skills, and improving overall quality of life. Patients expressed positive changes in self-perception, interpersonal relationships, and ability to manage symptoms. However, challenges such as stigmatization and lack of social support were also identified. This research concludes that mental health education programs have a significant impact on improving the well-being of patients with mental disorders. Recommendations are provided to increase program accessibility, reduce stigma associated with mental disorders, and strengthen social support for patients. Further research is needed to explore the effectiveness of this program over a longer period of time and in a broader population.